الأصول الفلسفية للنقد الثقافي The Philosophical Origins Of Cultural Criticism - دحومان, لخضر (جامعة الوادي - University of Eloued, 2020)
ملخص : تستند مناهج النقد الأدبي كلها إلى رؤى فلسفية تستمد منها مشروعيتها وآلياتها الإجرائية النقدية. والنقد الثقافي بدوره يستند إلى مثل هذه الرؤى. و قد تبين من دراستها باعتماد المنهج الوصفي أنها ترجع في عمومها لأصول فلسفية. وفي هذا المقال، نحاول الإجابة عن تساؤلات حول ماهية هذه الأصول، والممثلة إجمالا فيما يلي: 1-الثقافة. 2- ما بعد الحداثة. 3-الماركسية. 4- العولمة الثقافية. Summary: Literary criticism approaches are all relied on philosophical visions from which they derive their legitimacy and their critical procedures mechanisms. So that cultural criticism, in turn, is also based on such visions. Relying on the descriptive approach, this study highlighted that these visions were generally due to philosophical origins. So, through this paper, we try to answer several questions related to the concepts of these origins ,which are altogether consisted in the following items: 1- Culture. 2- Postmodernism. 3- Marxism. 4- Cultural globalization.
مقال
Keywords: أصول ؛ نقد؛ ثقافي؛ حداثة؛ عولمة; Origins. Cultural; Criticism; Modernism; Globalization